Effect of Extracts and Flour of Batak Onions on the Number of Escherichia Coli Colonies in Broiler - Wira Annisa; Achmad Sadeli; Ma'ruf Tafsin; Sayed Umar (Talenta Publisher, 2022)
This study aims to find out the effect of giving extracts and onion flour batak as a controller Escherichia coli also as an antibacterial in broiler chickens as well as to know the relative weight of the digestive organs of broiler chickens. The research method used is a complete randomized design (RAL) with 7 treatments and 3 replays. Treatment consists of Non-infectious Control (POA); Control+E.coli infection (POB); POA+Batak Onion Extract (A.chinense) concentration 20% dose 1 ml/tail (P1); POA+Batak Onion Flour (A.chinense) with a dose of 0.05% of the amount of feed given (P2); POB+Batak Onion Extract (A.chinense) concentration of 20% at a dose of 1ml/tail (P3); POB+Batak Onion Flour (A.chinense) with a dose of 0.05% of the amount of feed given (P4); POB+Tetracycli Antibiotic (P5). The result of this studies have an significant effect (P<0,05) on the decrease in the number of E.coli bacterial colonies in chicken digesta, batak onion (A.chinense) extract and flour were able to control E.coli bacteria. The treatment also had no significant effect (P>0,05) on the relative weight of the digestive. Based on this research, it can be concluded the giving of batak onion (A.chinense) extract and flour has an effect on E.coli bacteria and can be used as an alternative to antibiotics, but it does not effect the relative weight of the digestive organs of the chicken.